East German medical aid to Nicaragua: the politics of solidarity between biomedicine and primary health care - Iris Borowy (História, Ciências, Saúde: Manguinhos)
Abstract Between 1979 and 1989 the government of the German Democratic Republic provided health assistance to Sandinista Nicaragua. After initial relief aid, the Sandinista embrace of a primary health care-based health system made East German health support difficult. The non-convertible currency, the repressive quality of the East German leadership, and the lack of experience with primary health care processes all limited its potential to provide support. After 1985, when implementation of this system stalled, East German health assistance was revitalized with the donation of the Hospital Carlos Marx. Providing medical services to three hundred thousand people, it combined elements of a strictly East German institution, using German personnel and equipment, with some integration into local systems.